The Effect of Educational Game Method with Snakes and Ladders Media on Knowledge and Attitude of Fish Consumption among Elementary School Students - Jannah, Raudatul; Farhat, Yasir; Nurhamidi (Jurnal Riset Pangan dan Gizi, 2025)
Primary school children in Indonesia face nutritional problems that impact their growth. The results of the study at SDN Sungai Kuini 1 showed that the level of knowledge of fish consumption was mostly sufficient (37.5%), and less (62.5%). attitudes towards fish consumption showed a positive attitude (50%), moderately positive attitude and less each (25%). The purpose of this study was to determine the effect of educational game methods with snakes and ladders media on knowledge and attitudes towards fish consumption in elementary school students. This study used a quasi experiment method with a two group pretest posttest design with control group. The population consisted of 91 students, with a sample of 32 students taken using the Stratified Random Sampling method. The sample was divided into intervention group (three-dimensional snakes and ladders game) and control group (two-dimensional snakes and ladders game). Knowledge and attitude data were collected through interviews using questionnaires, and data analysis using the Paired Samples T Test and Independent Samples T Test. Statistical test results showed a difference in knowledge and attitude scores before and after treatment in each group (p < 0.05). The analysis also found significant differences in knowledge and attitude scores after treatment in each group (p < 0.05). However, based on the mean difference, the intervention group showed a more significant improvement in knowledge and attitude. The three-dimensional snakes and ladders game has been proven to have an effect in improving knowledge and attitudes. For future research, it is suggested that researchers can develop or use other educational media in the form of games to achieve more varied and in-depth results